A Study of District Heating Systems with Solar Thermal Based Prosumers. (September 2018) - Wang, Danhong; Orehounig, Kristina; Carmeliet, Jan
Abstract: The integration of heat production from solar energy technologies can be realized by feeding in energy both at centralized or at multiple decentralized locations from the consumer side. As distribution networks serve as thermal transmission grids, the interaction between the energy feed in (i.e. production) and withdrawal (i.e. consumption) at multiple locations within distribution networks should be incorporated. Modelling the interactions between these subsystems is challenging. This paper aims to study the potential of district heating system with solar thermal based prosumers, by developing a modelling framework for design and simulation of such networks. Quantitative comparisons are made on the system performances, by addressing key technical configurations and constraints of thermal networks and temperature dynamics of energy sources. In this paper, a comprehensive design and simulation model is built to assess the performance of different scenarios of district heating system designs with solar thermal based prosumers. Design variations are carried out by selection of different buildings in the district as prosumers. The simulation model framework is setup in Matlab, with hourly time step. The distribution network model is formulated as a thermal hydraulic model representing detailed information on thermal and hydraulic losses on each pipe. It enables bidirectional flow from multiple sources integrated into the district heating network. Energy conversion technologies (solar thermal collectors) and heat demand are connected with the network model as source and sink. A natural gas boiler acts as an additional base load heat source. The design and simulation framework is applied to an artificial case study, composed of 20 buildings with mixed building stocks including office and residential buildings.